Nghiên cứu lí thuyết cơ chế và động học của phản ứng giữa gốc propargyl (C3H3) với nguyên tử hiđro (H) bằng phương pháp phiếm hàm mật độ - Tiến, Phạm Văn (Vietnam Journal of Chemistry, 2017)
The reaction mechanism between propargyl radical and hydrogen atom has been studied by the Density Functional Theory (DFT) using the B3LYP functional in conjunction with the 6-311++G(3df,2p) basis set. The potential energy surface (PES) for the C3H3 + H system has been established. Our calculations show that the C3H3 + H reaction has two main entrance channels: H-abstraction and addition. The H-abstraction reaction pathway with relative energies (kcal.mol-1 is C3H3 + H (0) → T0/P11 (12.34) → HCCCH + H2 (-10.95). On the other hand, three addition reaction pathways with relative energies (kcal.mol-1) are found: C3H3 + H (0) → H2CCCH2 (-86.48), C3H3 + H (0) → H3CCCH (-87.46), and C3H3 + H (0) → H2CCHCH (-26.37). From three intermediates above, 10 other products and many isomers are formed. In terms of thermodynamic side, all of 11 products are possible to be produced at the investigated condition, in which the product of (H2CCC+H2) is the most favorable. Besides, calculation results of thermodynamics shown that many reaction channels are very close to data of NIST. Keywords. Reaction mechanism, propargyl radical, H atom, basis sets, DFT, PES